2015
DOI: 10.1002/ente.201500148
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Variations in Spark Timing using a Spark‐Ignition Engine with Hydrogen‐Blended Gasoline

Abstract: This study describes an experiment conducted using an electronically controllable single‐cylinder high‐speed gasoline engine to analyze the performance and emissions characteristics of various hydrogen–gasoline blends. The experiments have been conducted for various engine speeds and spark timings at the wide open throttle position. The experimental results revealed that the engine brake thermal efficiency and brake mean effective pressure first increase and then decrease with the increase engine speed at all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The results exhibited that H1 and H2 operations had slightly lower CO emissions compared to counter‐engine operations, but the values were too low in comparison to neat hydrogen. This can be attributed to the wide high flame speed and flammability range of hydrogen, which rapidly consumes oxygen and adjacent air from water–methanol, leading to a reduction in CO oxidation time and post‐combustion period resulting in lower CO emissions (Ji & Wang, 2009; Ma et al., 2010; Shivaprasad et al., 2015; Wan et al., 2021). As shown in Exhibit 12(a), it can be concluded that emissions of CO decrease for hydrogen, H1 and H2 operations compared to gasoline, but there is a slight increase as the speed of engine also increases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results exhibited that H1 and H2 operations had slightly lower CO emissions compared to counter‐engine operations, but the values were too low in comparison to neat hydrogen. This can be attributed to the wide high flame speed and flammability range of hydrogen, which rapidly consumes oxygen and adjacent air from water–methanol, leading to a reduction in CO oxidation time and post‐combustion period resulting in lower CO emissions (Ji & Wang, 2009; Ma et al., 2010; Shivaprasad et al., 2015; Wan et al., 2021). As shown in Exhibit 12(a), it can be concluded that emissions of CO decrease for hydrogen, H1 and H2 operations compared to gasoline, but there is a slight increase as the speed of engine also increases.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the HC emissions for all hydrogen-based fuels increased as engine speed increased. This can be accredited to the higher flame speed, shorter distance of quenching, and greater diffusivity of hydrogen, which increase the formation rate of OH radicals and thus reduce HC emissions (Chitragar et al, 2017;Ji et al, 2012;Shivaprasad et al, 2015Shivaprasad et al, , 2016. The water injection into the engine's intake manifold also influences the emission of HC.…”
Section: Hc Emissionmentioning
confidence: 99%
“…Shivaprasad et al [37,38] investigated the impact of hydrogen blending with gasoline in spark-ignition engines, indicating that a 20% hydrogen blend can improve engine efficiency and reduce emissions. While such blending has been shown to reduce HC and CO emissions, contributing to improved combustion efficiency, it is also associated with an increase in nitrogen oxide (NOx) emissions.…”
Section: Advances In Alternatives To Petroleum-based Fuelsmentioning
confidence: 99%
“…sources [1][2][3][4][5][6][7]. Hydrogen energy has received widespread attention for its clean, efficient, renewable and sustainable characteristics [8,9].…”
Section: Mini-review Articlementioning
confidence: 99%